2021
DOI: 10.1186/s12879-021-05982-3
|View full text |Cite
|
Sign up to set email alerts
|

Bittersweet: infective complications of drug-induced glycosuria in patients with diabetes mellitus on SGLT2-inhibitors: two case reports

Abstract: Background Sodium-glucose co-transporter 2 (SGLT2) inhibitors are novel hypoglycemic agents which reduce reabsorption of glucose at the renal proximal tubule, resulting in significant glycosuria and increased risk of genital mycotic infections (GMI). These infections are typically not severe as reported in large systematic reviews and meta-analyses of the medications. These reviews have also demonstrated significant cardiovascular benefits through other mechanisms of action, making them attract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…47 Another adverse effect that has consistently been reported involves genital mycotic infections related to glycosuria. 48 SGLT2 inhibitors have also been associated with rare but life-threatening Fournier’s gangrene of the perineum. 49 However, since the glycosuric effect of this drug dissipates beyond stage 3 CKD, the risk of euglycaemic DKA, genitourinary infections and even hypoglycaemia should not be of concern in the PD population.…”
Section: What Are the Safety Concerns For Sglt2 Inhibitor Use In Pd P...mentioning
confidence: 99%
“…47 Another adverse effect that has consistently been reported involves genital mycotic infections related to glycosuria. 48 SGLT2 inhibitors have also been associated with rare but life-threatening Fournier’s gangrene of the perineum. 49 However, since the glycosuric effect of this drug dissipates beyond stage 3 CKD, the risk of euglycaemic DKA, genitourinary infections and even hypoglycaemia should not be of concern in the PD population.…”
Section: What Are the Safety Concerns For Sglt2 Inhibitor Use In Pd P...mentioning
confidence: 99%
“…Even novel hypoglycemic agents that can induce glycosuria, most notably already mentioned SGLT2 inhibitors, can also increase the risk of genital candidiasis in males (Figure 2 ). For example, a recent report by Bartolo et al [ 73 ] showed the development of balanitis due to C. albicans and subsequent candidemia but also the potential role of other species such as C. glabrata . A severe form of balanoposthitis caused by C. albicans after treatment with SGLT2 was also described in a 57-year-old with type 2 diabetes coupled with oral candidiasis[ 74 ].…”
Section: Types Of Urogenital Candidiasis In Patients With Diabetesmentioning
confidence: 99%
“…Despite the broad benefits of SGLT2i, several adverse events have been reported, including euglycemic diabetic ketoacidosis, urinary tract infections (UTIs), genital mycotic infections with all the agents, and a risk of lower limb amputation with canagliflozin specifically [ 5 ]. A handful of case reports have described the occurrence of severe invasive fungal infections due to Candida in patients on SGLT2i [ 6‐9 ]. We describe a case of invasive Candida infection in a patient on empagliflozin following a prostate biopsy.…”
Section: Introductionmentioning
confidence: 99%